Considering Postoperative Functional Hypoaldosteronism after Unilateral Adrenalectomy. Issue 6 (June 2017) - Starker, Lee F.; Christakis, Ioannis; Julien, Jamii; Schwarz, Kelly; Graham, Paul; Grubbs, Elizabeth G.; Lee, Jeffrey E.; Perrier, Nancy D.
Conn's Syndrome is an uncommon condition. Patients who have undergone adrenalectomy in the early postoperative period can demonstrate biochemical hypoaldosteronism. Given the rare nature of this phenomenon we investigated its incidence and whether it translated to clinical findings. A single-institution retrospective review of all patients with biochemically proven hyperaldosteronism from 2005 to 2014 that underwent unilateral adrenalectomy. A total of 29 patients fit the inclusion criteria. Functional hypoaldosteronism had appreciated in 18/29 (62%) patients, whereas 11 patients (38%) had normal postoperative aldosterone. No significant differences between diagnostic groups were found in terms of clinical outcomes (length of stay, postoperative symptomatology, and readmissions P = 0.669, 0.154, and 0.268, respectively). Two (7%) patients required medical therapy. Biochemical evidence of functional hypoaldosteronism was identified in two-thirds of patients undergoing unilateral adrenalectomy. Although contralateral aldosterone suppression can be anticipated, the phenotypic response varied and the outcomes were similar to patients with normal aldosterone levels. Current guidelines make no formal recommendations for assessment of hypoaldosteronism after adrenalectomy, resulting in varying practice paradigms. Surgeons should consider the risk of postoperative hypoaldosteronism in these patients and counsel patients accordingly. Prospective investigations should be performed to assist in development of an outcomes-based care delivery model for these patients.